UNSUR KOMPETENSI GURU DALAM KITAB USHUL AT-TARBIYAH WA TA’LIM SEBAGAI DUKUNGAN TERHADAP KEBIJAKAN PENDIDIKAN NASIONAL DI PESANTREN - Farichah, Ainun; Hasibullah, Muhamad Umar (International Conference on Humanity Education and Society (ICHES), 2025)
This study aims to explore and identify various elements of teacher competence contained in the book Ushul At-Tarbiyah Wa Ta'lim, which is used in the education process in the pesantren environment. These competencies are analysed and compared with the teacher competency standards as stated in the Law of the Republic of Indonesia Number 14 of 2005. This research uses the literature study method with a philosophical approach as the basis for analysis. Law Number 14 of 2005 states that there are four main dimensions in teacher competence, namely pedagogic, personality, professional, and social competence. These four aspects are also found in the book Ushul At-Tarbiyah Wa Ta'lim as fundamental elements in the formation of teacher competence. After being analysed in depth and linked to the context of today's education, the competency content in the book is proven to be relevant and can be used as a reference in developing learning strategies and practices in educational institutions, especially pesantren.